Study of Education Competency and Effect on Learning Process of BCCT Method on Educational Group of Education Age (PAUD) in Sukasari Bandung - Yulisutiany, Irma (International Journal of Educational Technology and Learning, 2018)
The purpose of this research is to describe the objective condition of PAUD Kober Nurul Huda. Describe the level of competence that educators have. Describe the application of learning through the BCCT Method. Know the influence of the application of learning BCCT Method. The research method used is a qualitative method of research subject is Kober Nurul Huda. Data collection methods used are methods of observation, interviews, and documentation. The conclusion of this research is the objective condition of PAUD Nurul Huda has the strength which generally comes from facility, location, and education of the educator, weakness is found in the competence of educator in giving learning of BCCT, opportunity to potential of parent desire to send their child to PAUD applying BCCT , and threats from environmental influences that are contrary to the concept of BCCT itself. The competencies of PAUD Nurul Huda educators include pedagogic competence, personality competence, physiological competence, but generally still weak on social competence. The application of learning through the BCCT method of Kober Nurul Huda can optimize all aspects of children’s development, whether physical, emotional, cognitive, and social. The influence of learning through BCCT methods of learners is seen primarily in the moral and religious values, cognitive learners, the use of everyday language, the emotional social of children, creativity, the soul of art, and life skills. The recommendations proposed are practical, the playgroup Nurul Huda should make education more creative in providing learning, educators need to develop and practice in running learning, the foundation should provide facilities to educators to include them in BCCT training held Diknas city or province. Theoretically, developing theories about the aspects of the learner, so the results of this study can develop the success rate of learners together with the discipline of psychology.